Geographic distribution of sex chromosome polymorphism in Anastrepha fraterculus sp. 1 from Argentina - Giardini, Maria Cecilia; Nieves, Mariela; Scannapieco, Alejandra Carla; Conte, Claudia Alejandra; Milla, Fabian Horacio; Schapovaloff, Maria Elena; Frissolo, Maria Soledad; Remis, Maria Isabel; Cladera, Jorge Luis; Lanzavecchia, Silvia Beatriz (BioMed Central, 2021)
Background Anastrepha fraterculus is recognized as a quarantine pest in several American countries. This fruit fly species is native to the American continent and distributed throughout tropical and subtropical regions. It has been reported as a complex of cryptic species, and at least eight morphotypes have been described. Only one entity of this complex, formerly named Anastrepha fraterculus sp. 1, is present in Argentina. Previous cytogenetic studies on this morphotype described the presence of sex chromosome variation identified by chromosomal size and staining patterns. In this work, we expanded the cytological study of this morphotype by analyzing laboratory strains and wild populations to provide information about the frequency and geographic distribution of these sex chromosome variants. We analyzed the mitotic metaphases of individuals from four laboratory strains and five wild populations from the main fruit-producing areas of Argentina, including the northwest (Tucumán and La Rioja), northeast (Entre Ríos and Misiones), and center (Buenos Aires) of the country.